2015
DOI: 10.11648/j.ajim.20150302.11
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Ulcer: A Review

Abstract: Diabetic foot problems are common throughout the world, resulting in major medical, social and economic consequences for the patients, their families, and society. Foot ulcers are more likely to be of neuropathic origin, and therefore eminently preventable. People at greatest risk of ulceration can easily be identified by careful clinical examination of the feet: education and frequent follow-up. Infection when complicates a foot ulcer, combination can be limb or life-threatening, and infection is defined clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 141 publications
1
26
0
1
Order By: Relevance
“…This suggests that the occurrence of diabetic foot ulcers occurs in the fifth and sixth decades. 7,9 The age group with the most diabetic foot ulcers was age over 60 years (45.9%) followed by age 50-59 years (35.2%) and the lowest at 40-49 years old (18.9%), this is also explained by Zubair et al (2015), that the prevalence of diabetic foot ulcers increases with age over 40 years. 1 In a study conducted by Manda et al, there was also a distribution of diabetic foot ulcers found in more than 75 percent aged 30 to 60 years, and the highest number at age 50-59 years (42.5%).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This suggests that the occurrence of diabetic foot ulcers occurs in the fifth and sixth decades. 7,9 The age group with the most diabetic foot ulcers was age over 60 years (45.9%) followed by age 50-59 years (35.2%) and the lowest at 40-49 years old (18.9%), this is also explained by Zubair et al (2015), that the prevalence of diabetic foot ulcers increases with age over 40 years. 1 In a study conducted by Manda et al, there was also a distribution of diabetic foot ulcers found in more than 75 percent aged 30 to 60 years, and the highest number at age 50-59 years (42.5%).…”
Section: Discussionmentioning
confidence: 91%
“…7,9 The age group with the most diabetic foot ulcers was age over 60 years (45.9%) followed by age 50-59 years (35.2%) and the lowest at 40-49 years old (18.9%), this is also explained by Zubair et al (2015), that the prevalence of diabetic foot ulcers increases with age over 40 years. 1 In a study conducted by Manda et al, there was also a distribution of diabetic foot ulcers found in more than 75 percent aged 30 to 60 years, and the highest number at age 50-59 years (42.5%). 9 Description of the minimum value of GDP, GD2JPP and HbA1c still shows normal levels, this indicates that diabetic foot ulcers have been treated in DM disease control efforts, but the average grade is still high wherein GDP 180.95 (SD 71.4) mg/dl, 2 hours PP blood sugar with a mean value of 263.14 (SD 100.43) mg/dl, and HbA1c with a mean grade of 8.13 (SD 1.96).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The prevalence of 6.1 percent in individuals aged above 40 years was unexpectedly high at that time for rural area with low socio-economic status and decreased health awareness. [11] …”
Section: Epidemiologymentioning
confidence: 99%